Effect of the physicochemical properties of zinc oxide sources on their bioavailability in broilers. Issue 6 (2nd November 2021) - Cardoso, D.; Romeo, A.; Durosoy, S.; Meme, N.; Chevalier, Y.; Narcy, A.
ABSTRACT: 1. The bioavailability of a trace mineral source is related to its intestinal solubility (bioaccessibility), which in turn is determined by its physicochemical properties. It is still not clear which characteristics are more relevant in affecting solubility and bioavailability of mineral sources. Zinc oxide (ZnO) is a common feed additive used to supplement zinc in the diet of monogastric animals. However, different sources have shown variable responses on animal bioavailability. 2. This study hypothesised that different sources of feed grade ZnO have various physicochemical features that lead to distinct bioavailability values. Feed grade ZnO samples collected from the feed industry worldwide were characterised for their physicochemical features and tested in broilers to allow bioavailability determined. 3. A total of 135 male Cobb broiler chickens were fed a standard starter diet from day 1 after hatching up to d 7. At d 8, animals were allocated in individual cages and fed one of the following dietary treatments during 15 days: a basal diet with 23.5 ppm of zinc and seven test diets with supplemented ZnO or zinc sulphate (ZnSO4 ) at 6 or 12 ppm. 4. Different sources of ZnO showed an effect of solubility in the stomach and supplementation influenced total Zn levels in the ileum. The bioavailability of the different sources varied from 49% to 160% in relation to ZnSO4 . Aggregate size of particles seems to explain most of the variability in the bioavailability of the different sources tested in broilers. In conclusion, physicochemical properties of ZnO can partly explain the variability observed in terms of biological value.